(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
This article provides an in-depth analysis of the role of folk customs and traditions in folklore and examines folk songs as a ritual-musical phenomenon within the cultural space of Uzbekistan, with particular emphasis on the Surkhan oasis. The research explores how customs and traditions function as stable socio-cultural mechanisms embodied in folklore genres and how folk songs serve as a primary medium for transmitting ritual, ethical, and aesthetic values. Using interdisciplinary methods, including cultural-anthropological, folkloristic, and ethnomusicological analysis, the study identifies the distinctive features of Surkhandarya folk songs, emphasizing their ritualistic integrity, functional stability, and symbolic richness. The findings demonstrate that folk songs in the Surkhan oasis play a crucial role in preserving collective memory and sustaining cultural continuity.